Product quality, measured inflation and monetary policy - Alexander Rodnyansky; Alejandro Van der Ghote; Daniel Wales (European Central Bank (ECB), 2022)
This paper proposes a tractable New Keynesian (NK) economy with endogenous adjustment in product quality that nests the canonical framework. Endogenous quality choice reduces the slope of the traditional NK Phillips curve and ampliffes the economy's response to productivity shocks. This leads to a less reactionary monetary policy where model misspeciffcation of imperfectly observable quality adjustments matters more for macroeconomic stabilization than the mismeasurement of those adjustments. With no misperception of product quality by the monetary authority, the principles for optimal monetary policy are, nonetheless, unchanged as the quality extensions to the canonical NK model preserve divine coincidence.
Keywords: E31; E32; E52; E58; 330; Product Quality; Inflation Indexes; Monetary Policy